2013
DOI: 10.1186/1471-2466-13-40
|View full text |Cite
|
Sign up to set email alerts
|

The health economic impact of disease management programs for COPD: a systematic literature review and meta-analysis

Abstract: BackgroundThere is insufficient evidence of the cost-effectiveness of Chronic Obstructive Pulmonary Disease (COPD) Disease Management (COPD-DM) programs. The aim of this review is to evaluate the economic impact of COPD-DM programs and investigate the relation between the impact on healthcare costs and health outcomes. We also investigated the impact of patient-, intervention, and study-characteristics.MethodsWe conducted a systematic literature review to identify cost-effectiveness studies of COPD-DM. Where f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 36 publications
(137 reference statements)
2
49
0
6
Order By: Relevance
“…These programs aim to coordinate guideline-informed outpatient care for patients with chronic diseases. 38,39 Chronic disease management programs also address hospital readmissions and mortality, although these are not important issues for FGIDs. 36 Similar programs in diabetes, 37 chronic obstructive pulmonary disease, and cirrhosis care have shown similar improved outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These programs aim to coordinate guideline-informed outpatient care for patients with chronic diseases. 38,39 Chronic disease management programs also address hospital readmissions and mortality, although these are not important issues for FGIDs. 36 Similar programs in diabetes, 37 chronic obstructive pulmonary disease, and cirrhosis care have shown similar improved outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Three systematic reviews have shown clinical benefits, finding a significant reduction in both exacerbations requiring medical attention, and in the frequency of hospitalizations, improvements in exercise tolerance and shorter hospital stays. [16][17][18] In a fourth meta-analysis, Boland et al 19 also showed a reduction in direct costs, with savings of D 1060 (95% CI: D 80-D 2040) per patient and year in hospitalization costs and D 898 (95% CI: D 231-D 1566) in costs derived from the use of healthcare services. However, the heterogeneity of the interventions, with underpowered pilot studies, and the scant methodological use of clinical trials make it difficult to draw definitive conclusions.…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 95%
“…; Brady, ; de Bruin et al., Dongbo et al., ; 2011; Tsiachristas et al., ; Boland et al. ; van Steenbergen‐Weijenburg et al., ).…”
Section: Taxonomy Of Health Care Programmesunclassified